PROSODIC ASPECTS IN ORAL READING (Muitas Vozes, 2021)
The Prosodic Markers of Writing (CAGLIARI, 1989, 2002a, 2002b) are traits that carry prosodic information from graphic resources that give the reader the possibility of translating in his/her oral reading the prosodic elements existing in speech. The orality of the text can be reconstituted with the translation of the writing and the textual markings, thus the many existing resources in writing, such as punctuation marks, need to be expressed in the reading aloud through the characteristics inherent to speech, this recovery should be carried out by the reader in order to engender the written text closest to the oral language. The aim of this work is to present some prosodic elements of writing and their possible expressions in oral reading, especially in the context of basic education in Brazil, problematizing the reading fluency and linguistic knowledge of these agents.